2022
DOI: 10.7759/cureus.24432
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Proactive Rounding Team on Rapid Response System During COVID-19 Pandemic: A Retrospective Study From an Italian Medical Center

Abstract: Objective: During the coronavirus disease 2019 (COVID-19) pandemic a proactive rounding (PR) team was introduced in our clinical practice in order to recognize the clinical deterioration of the patient as soon as possible. This study aimed to evaluate the impact of the PR team on the rapid response system (RRS) workload with particular regard to the activity carried out, the mode of intervention, and the outcome of patients. Methods: In this retrospective study, the first period before the activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…1 for additional details of the screening process. Most studies reviewed fit within two categories: they examined the effects of rapid response implementation on patient outcomes ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Chen et al., 2015 ; Davis et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Mankidy et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ), or they described rapid response systems and their associations with patient characteristics and outcomes ( Jung et al., 2022 ; Winterbottom and Webre, 2021 ; Avis et al., 2016 ; Bunch et al., 2019 ; Chan et al., 2016 ; Churpek et al., 2017 ; Jones et al., 2017 ; Kollef et al., 2017 ; Le Guen et al., 2015 ; Psirides et al., 2016 ; Silva et al., 2016 ; Smith et al., 2015 ; Stelfox et al., 2015 ; Sulistio et al., 2015 ). Generally, rapid response system implementation studies included scenarios in which the system implemented was the first iteration of its kind ( Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ), was replacing an existing system ( Aitken et al., 2015 ), or added another tier of clinical experience or surveillance to an existing system ( Davis et al., 2015 ; Kawaguchi et al., 2015 ; Pirret et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 for additional details of the screening process. Most studies reviewed fit within two categories: they examined the effects of rapid response implementation on patient outcomes ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Chen et al., 2015 ; Davis et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Mankidy et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ), or they described rapid response systems and their associations with patient characteristics and outcomes ( Jung et al., 2022 ; Winterbottom and Webre, 2021 ; Avis et al., 2016 ; Bunch et al., 2019 ; Chan et al., 2016 ; Churpek et al., 2017 ; Jones et al., 2017 ; Kollef et al., 2017 ; Le Guen et al., 2015 ; Psirides et al., 2016 ; Silva et al., 2016 ; Smith et al., 2015 ; Stelfox et al., 2015 ; Sulistio et al., 2015 ). Generally, rapid response system implementation studies included scenarios in which the system implemented was the first iteration of its kind ( Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ), was replacing an existing system ( Aitken et al., 2015 ), or added another tier of clinical experience or surveillance to an existing system ( Davis et al., 2015 ; Kawaguchi et al., 2015 ; Pirret et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Broad patterns of what rapid response system components were reported on in included studies were also assessed. A majority of studies (27 of 34) identified what rapid response system triggers were used ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Chen et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Jung et al., 2022 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ; Bunch et al., 2019 ; Churpek et al., 2017 ; Kollef et al., 2017 ; Le Guen et al., 2015 ; Psirides et al., 2016 ; Silva et al., 2016 ; Smith et al., 2015 ; Stelfox et al., 2015 ; Sulistio et al., 2015 ); additionally, a majority of studies (28 of 34) also included at least some details related to member composition of their medical emergency teams ( Roasio et al., 2022 ; Aitken et al., 2015 ; Al-Rajhi et al., 2016 ; Blotsky et al., 2016 ; Davis et al., 2015 ; Davis et al., 2015 ; Jung et al., 2016 ; Kawaguchi et al., 2015 ; Kim et al., 2017 ; Ludikhuize et al., 2015 ; Jung et al., 2022 ; Menon et al., 2018 ; Noyes et al., 2015 ; Pirret et al., 2015 ; Gong et al., 2020 ; Mankidy et al., 2020 ; Oh et al., 2018 ; Viana et al., 2021 ; Yang et al., 2020 ; Winterbottom and Webre, 2021 ; Avis et al., 2016 ; Bunch...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 , 3 Low implementation may be attributed to few descriptions of successful pediatric programs in the literature and limited evidence for its benefit. 14 , 20 , 21 , 22 In this study, we describe the core features of a successfully implemented critical care outreach team within a fully resourced RRS. Core features of our CCOT include dedicated personnel for managing critical illness outside of the ICU, close integration with existing RRS processes to identify at-risk children, and in-person rounds to foster collaboration between ward and ICU teams.…”
Section: Discussionmentioning
confidence: 99%